PENGARUH SALES PROMOTION, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PENGGUNA GOFOOD DI KOTA JAKARTA TIMUR - Adinda Permatasiwi, (2023)
This type of research is quantitative research which has the aim of partially determining the effect of sales promotion, price, and service quality on customer satisfaction of Gofood users in East Jakarta. The population in this study are active users of the Gofood application who are more than 17 years old and live in the city of East Jakarta, and the sample set in this study was 100 respondents. In sampling using purposive sampling technique. Data collection was carried out in this study by distributing questionnaires online through social media with the help of google form. In this study using the SEM method with the help of software SmartPLS 4.0. The results obtained from this study are 1) Sales promotion has a significant influence on customer satisfaction, 2) Price has not a significant influence on customer satisfaction, 3) Service quality has a significant influence on customer satisfaction.